2003
DOI: 10.2754/avb200372010115
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Bovine Respiratory Syncytial Virus in Cell Cultures by nRT-PCR and Use of the Method for Virus Identification in Clinical Samples

Abstract: One-step RT-PCR and nested PCR were used to detect bovine respiratory syncytial virus (BRSV) in infected cell cultures. Specific 984 bp and 383 bp products, selected from gene encoding the F protein using suitable primers, were amplified and, if appropriate, reamplified. The method was further used for examination of nasal swabs and blood samples collected from animals showing signs of a respiratory disease. Lactating cows and 6-8-month-old bulls from two herds were investigated.The infection by BRSV was confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Diagnosis of BRSV isolated from nasal samples was determined using nested RT-PCR technique through a couple of primers target against (G) gene in nasal samples which indicate the accuracy and efficacy of the PCR technique for identification of BRSV in naturally infected cattle. This method can be used as a powerful technique in epidemiological studies, as reported in previous studies (Vilcek et al,1994;Valentova et al, 2003;Almeida et al, 2006). The result obtained in this study demonstrated that the G gene is very conservative and can be utilized as a target sequence for the identification of BRSV through RT-PCR.…”
Section: Discussionsupporting
confidence: 70%
“…Diagnosis of BRSV isolated from nasal samples was determined using nested RT-PCR technique through a couple of primers target against (G) gene in nasal samples which indicate the accuracy and efficacy of the PCR technique for identification of BRSV in naturally infected cattle. This method can be used as a powerful technique in epidemiological studies, as reported in previous studies (Vilcek et al,1994;Valentova et al, 2003;Almeida et al, 2006). The result obtained in this study demonstrated that the G gene is very conservative and can be utilized as a target sequence for the identification of BRSV through RT-PCR.…”
Section: Discussionsupporting
confidence: 70%
“…We have isolated BHV-4 from nasal swabs obtained from calves (CH isolate) and dairy cows (Ni isolates) with respiratory distress. Duplicate serum samples from calves revealed elevated antibody titre against BRSV, although the virus could not be detected in clinical samples by specific nested RT-PCR (Valentova et al, 2003). Serum samples from cows were not available.…”
Section: Discussionmentioning
confidence: 97%
“…Virus isolation was not attempted, since it is not considered to be a practical diagnostic method of choice (Vilcek, et al, 1994) as the viral isolation is complicated by the high sensitivity of the agent and the fact that several passages are necessary before CPE develops (Valentova and kovarcik, 2003). Also the isolation is a laborious procedure with unpredictable results because animal that develop the disease are not the best of choice as in most cases of BRSV or BPI-3 is obtained during isolation procedures for other viral pathogens rather than procedure specifically carried out for those viruses (Arns, et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Several RT-PCR for RSV detection based on the fusion (F) gene (Vilček, et al, 1994;Van der poel, et al, 1997 andValentova, et al, 2003) have been developed and evaluated in studies involving numerous field specimens. Therefore RT-PCR is potentially useful for improving the sensitivity of RSV detection.…”
Section: Discussionmentioning
confidence: 99%